Efektivitas Penggunaan Instagram Stories pada Akun @male.id terhadap Pembentukan Brand Awareness dan Minat Beli di Kalangan Mahasiswa Universitas Islam Indonesia - Putra Muhammad Dafa; Puji Hariyanti (Program Studi Ilmu Komunikasi UII, 2021)
Male.id as a local male fashion brand uses Instagram stories as a medium to introduce or promote their products to public and also to engage followers to interact by online. Therefore, this research is being done to analyze how effective the use of Instagram stories on @male.id’s account for the formation of brand awareness and purchase intention among the students of Islamic University of Indonesia. This research is a survey research with a quantitative approach, so the datas were collected by distributing questionners to 100 respondents who are determined through a nonprobability sampling technique in the form of snowball sampling to be sampled. This research shows that the use of Instagram on @male.id’s account is significantly effective and positive for the formation of brand awareness and purchase intention among students of Islamic University of Indonesia.